2018
DOI: 10.1111/jre.12565
|View full text |Cite
|
Sign up to set email alerts
|

The directional and non‐directional associations of periodontitis with chronic kidney disease: A systematic review and meta‐analysis of observational studies

Abstract: This systematic review aimed to assess the current evidence on the directional and non-directional associations of periodontitis with chronic kidney disease (CKD). Electronic search for observational studies on the association of periodontitis with CKD was performed in MEDLINE, EMBASE, PubMed, Open GREY and Cochrane library up to June 5, 2017. Two reviewers conducted study selection, data collection and assessment of methodological quality using the original and modified Newcastle-Ottawa Scale. Cohort, case-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 82 publications
(187 reference statements)
2
63
0
2
Order By: Relevance
“…; Zhao et al . ). These two conditions which have significant interactions with each other may facilitate the development of CVD in this patient population.…”
Section: Literature Reviewmentioning
confidence: 97%
See 3 more Smart Citations
“…; Zhao et al . ). These two conditions which have significant interactions with each other may facilitate the development of CVD in this patient population.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Periodontitis is also a common problem in patients with CKD (Akar et al 2011;Tiwari et al 2013) and it is thought that CKD and periodontitis could affect the course of each other. While periodontitis could facilitate the development of chronic inflammation in this patient population (Wasserman et al 2003), CKD could mechanistically influence the onset and/or progression of periodontal disease, possibly mediated by systemic risk factors including diabetes and hypertension and local risk factors such as xerostomia (Le Gall et al 2016;Zhao et al 2018). These two conditions which have significant interactions with each other may facilitate the development of CVD in this patient population.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, a large population‐based study did not corroborate the initial observations (Shin, ). Although a recent systematic review observed a robust body of evidence on the non‐directional association of periodontitis and CKD, studies reporting directional associations are still scarce (Zhao et al, ). It is important to highlight that the current literature presents some limitations including secondary analysis of subgroups, partial‐mouth protocols of periodontal examinations, case definition of periodontal disease and lack of a better description of medical status study participants.…”
Section: Introductionmentioning
confidence: 99%